ANISOTROPY OF FERROMAGNETIC MATERIALS - Radwan, Faeq A. A. (Transactions on Engineering and Computing Sciences, 2014)
The decomposition of elastic constant tensor into its irreducible parts is given. The norm of elastic constant tensor and the norms of the irreducible parts of the elastic constants of ferromagnetic materials (the elements Fe, Ni and Co and some of their alloys) are calculated. The relation of the scalar parts norm and the other parts norms and the anisotropy of the ferromagnetic materials are presented. The norm ratios are used to study anisotropy of ferromagnetic materials and the relationship of their structural properties and other properties with their anisotropy are given.